Teacher Feedback and Wait-Time in Primary Science Classroom Dialogue: A TBLA Study - Dessy Norma Juita; Venna Puspita Sari; Laely Farokhah (Universitas Negeri Padang, 2026)
This study explores how teacher feedback and wait-time shape the quality of classroom dialogue in primary science learning. Using a qualitative descriptive approach with Transcript-Based Lesson Analysis (TBLA), the study involved one sixth-grade science teacher and 19 students in an urban primary school in Tangerang Selatan, Indonesia. Data were collected through audio-visual recordings of three science lessons, classroom observations, and semi-structured interviews. The findings showed that accepted feedback was the most dominant type, mainly functioning to confirm students’ responses and maintain classroom flow. Modified feedback contributed more significantly to extending dialogue through probing questions and clarification prompts. Short wait-time tended to produce rapid and simple responses, whereas extended wait-time supported elaboration, reflection, and deeper reasoning. Furthermore, feedback and wait-time jointly contributed to the transformation of conventional IRF patterns into more dialogic IRFRF interaction sequences characterized by elaboration, reciprocity, reflection, and collaborative reasoning in primary science classroom discourse